Effect of the coagulation/persulfate pre-treatment to mitigate organic fouling in the forward osmosis of municipal wastewater treatment. (1st November 2019) - Pramanik, Biplob Kumar; Shu, Li; Jegatheesan, Veeriah; Bhuiyan, Muhammed A.
Abstract: The forward osmosis (FO) membrane process has recently established in many applications such as desalination, wastewater reuse, water purification, food processing, resource recovery and sustainable power generation. However, many researchers raise the demand for systematic investigation on FO membrane fouling, which leads to reduced flux yield. In this study, the effect of coagulation/persulfate as a feed pre-treatment was used to mitigate FO organic fouling during municipal wastewater treatment, and compared with a control coagulation and potassium persulfate pre-treatments. Mass balance results using size exclusion chromatography exhibited that the decrease in the flux with consecutive filtration cycles was likely due to humic-like molecules in the feedwater. Coagulation/persulfate contributed to a more significant flux improvement than stand-alone coagulation or persulfate pre-treatment, resulting in a smaller amount of organics attachment to the membrane. A better flux enhancement by coagulation/persulfate was again evidenced by a higher decrease in the attachment of reversible and irreversible organic foulants on the membrane surface. This study identified the major organic components responsible for FO fouling and established the potential of coagulation/persulfate pre-treatment for reducing organic fouling of FO membrane during municipal wastewater treatment. Graphical abstract: Image 1 Highlights: Major organic molecules responsible for FO fouling were identified. Ferric/potassium persulfate pretreatment enhanced the membrane flux. Ferric/potassium persulfate was effective to eliminate UV-absorbing compounds. The flux decline with consecutive cycles was mainly due to humic-like molecules. Osmotic backwashing was unable to full recover of FO performance with multi-cycles.